حوادث المرور تحليلها ومسبباتها وآثارها دراسة حالة : منطقة النواحي الاربعة (Comprehensive Journal of Science, 2025)
This study aims to identify traffic accidents in  the region of  Al-Nawayah Al-Arba'a - Libya, relying on data and annual reports from the Traffic Statistics Office of the Four Regions Security Directorate. The study also used the descriptive analytical approach to interpret and analyze the data collected on the study topic, with the aim of identifying the causes of traffic accidents and their geographical distribution on the roads in the region. Among the most important results reached by the study is that the number of accidents in the study area amounted to approximately (813) traffic accidents, resulting in (246) deaths, (639) serious injuries, in addition to (349) minor injuries. The study also found that most accidents occurred on the main road, reaching (548) traffic accidents, representing (44.4%) of the total accidents in the study area. The age group (25-45) years is the largest age group affected by traffic accident injuries and the largest number of deaths due to accidents, with a total of (68) deaths, including (52) males and (15) females. The study recommended the need for regular road maintenance, the installation of traffic signs, and the implementation of traffic laws.